Development of Purification and crystallization of sweet potato sugar - Tan, Felicia Li Hia (Universiti Malaysia Sarawak (UNIMAS), 2013)
Sweet potato (Ipomoea batatas) sugar can be obtained from purification and crystallization of the sugar syrups. Sweet potato contain 20 to 30 percent starch according to hydrolysis of starch into sugar makes it a potential alternative source of glucose for numerous applications. Liquid sugar was produced from hydrolysis of freshly blended sweet potato tubers. Two basic steps of enzymatic hydrolysis were carried out, namely liquefaction and saccharification involving two enzymes Termamyl-120L and Dextrozyme. Commercial sweet potato flour (SPF) was used as a control to compare with the fresh sweet potato (FSP) starch for their starch and glucose recovery. Glucose produced from enzymatic hydrolysis was purified by PAC filtration using 5 g and 109 PAC and subsequently crystallized in refrigerator prior for drying in desiccators to obtain sweet potato sugar. Glucose concentration of fresh sweet potato sugar (FSPS) and sweet potato flour sugar (SPFS) obtained after enzymatic hydrolysis were 42.83 gIL and 202.48 gIL, respectively. Starch recovery from FSP and SPF were 38.94% and 46.55%. Recovery of glucose obtained from FSPS and SPFS when using 5 g PAC were 85.62% and 83.82%, respectively. Conversely, there were 79.38% and 79.33%, respectively obtained when using 109 PAC. Although the glucose recovery of FSPS is slightly higher, it is recommended to use SPFS because it is cheaper and the difference of glucose recovery is only 2%. Hence, this indicated that sugar production from sweet potato starch (commercial SPF) can be produced by the method of purification and crystallization developed from this study.